Study guides

Q: -6x plus 3 plus 1 5?

Write your answer...

Submit

Related questions

The value of X in the equation 2x-1-6 5 plus 6x is -3.

Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5

6x + 3 = 2x + 5 4x = 2 x=1/2

If: 6x-4+7 = 5 Then: x = 1/3

y=(6x-5)/3

24x^3 + 72x2 + 30x = 6x*(4x^2 + 12x + 5)=6x*(2x + 1)*(2x + 5)

x2 + 6x + 5 can be factored into (x+1) (x+5)

34x + 72 is the answer to the equation 12 plus 6x-4 5 plus 2 3x-1.

6x-4+7=-5 6x+3=-5 6x=-8 x=-8/6 = -4/3

x squared +6x +5 is a quadratic expression that can be factored as (x+1)(x+5)

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

x2 - 6x + 5 = (x - 1)(x - 5)

If we recall that (5 cows plus 1 cow) = 6 cows, it immediately becomes apparent that5x plus 1x = 6x.

Multiplying out the brackets it then is: 6x+8x+8-3 = 14x+5 when simplified

(6x + 5)(6x + 5) or (6x + 5)2

x = 3/5 and y = 1/5

-3*6x+5/8=6x-1 * (-3*(6x+5))/8?If this is your question, then:LHS = -3 * 6x + 5/8 = -18x + 5/8RHS = 6x - 1 * (-18x-15)/8 = 6x + (18x+15)/8 = 48x/8 + 18x/8 + 15/8 = 66x/8 + 15/8-18x + 5/8 = 66x/8 + 15/866x/8 + 18x = 15/8 - 5/8210x/8 = 10/8210x = 10x = 10/210 = 1/21

6x + 15 = 12; so 6x = 12-15; 6x = -3 and x = -3 /6 = -.5 or - 1/2 The answer is negative one half.

(6x^5-4x^2)+(2x^3-3) = 6x^5-4x^2+2x^3-3 The grestest exponent is 5, which is the degree of the above expression.

(x + 5)(x + 1)

It is (x+5)(x+1) when factored

Factors are (x + 5)(x + 1) so x = -5 or -1

Assuming that the first operator is 6x^2. The factors are (6x-5)*(x-1)

x2+6x+5=0(x+1)(x+5)=0x=-1 and x=-51-6+5=0 and 25-30+5=0 so both answers work.

5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6